2013
DOI: 10.1039/c3fo30374h
|View full text |Cite
|
Sign up to set email alerts
|

Microencapsulation of tannic acid for oral administration to inhibit carbohydrate digestion in the gastrointestinal tract

Abstract: The prevalence of diabetes mellitus and obesity is rapidly rising worldwide. Recently, there is increasing evidence that phytochemicals such as polyphenols in our diet could directly inhibit the activities of key digestive enzymes, representing a novel method of controlling and preventing diabetes mellitus and obesity. More research is required to determine how to effectively utilize phytochemicals within the gastrointestinal (GI) tract to obtain maximum inhibition of digestive enzymes. This study investigated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
15
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 27 publications
1
15
0
Order By: Relevance
“…Encapsulation efficiency of SCT in KEMS by the aqueous ethanol method was similar to that obtained by other workers who encapsulated tea catechins in chitosan-tripolyphosphate nanoparticles (Hu, Pan, Sun, Hou, Ye, Hu & Zeng, 2008) and tannic acid in calcium alginate microspheres (Zhao et al, 2013) using coacervation. …”
Section: Sct Encapsulationsupporting
confidence: 62%
See 1 more Smart Citation
“…Encapsulation efficiency of SCT in KEMS by the aqueous ethanol method was similar to that obtained by other workers who encapsulated tea catechins in chitosan-tripolyphosphate nanoparticles (Hu, Pan, Sun, Hou, Ye, Hu & Zeng, 2008) and tannic acid in calcium alginate microspheres (Zhao et al, 2013) using coacervation. …”
Section: Sct Encapsulationsupporting
confidence: 62%
“…Zhao, Iyer, Flores, Donhowe & Kong (2013) demonstrated that by encapsulating tannic acid in calcium alginate microspheres, α-amylase could be substantially inhibited in the small intestine phase in a simulated gastrointestinal digestion. Kafirin, the sorghum prolamin storage protein, is notably hydrophobic and resistant to pepsin digestion (Belton, Delgadillo, Halford & Shewry, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Binding of polyphenols with protein molecules is driven by hydrogen bonding or hydrophobic interaction leading to the formation of soluble or insoluble polyphenol-protein aggregates. [32][33][34] The main features of the polyphenol structure that influence their interactions with protein have been reported to be the number of galloyl ester groups and the degree of polymerization. 35 In fact, heat changes associated with the addition of a model proline-rich peptide to non-galloylated monomers (catechin and epicatechin) were negligible compared to the addition of galloylated monomers (epicatechin gallate, with binding constant of 8.1 × 10 4 M −1 ) and especially to flavanol oligomers (mean degree of polymerization 4, with binding constant of 34.3 × 10 4 M −1 ).…”
Section: Inhibition Of α-Amylase By Winemaking Byproductsmentioning
confidence: 99%
“…10 A reaction mixture of starch solution (1%) and α-amylase solution (1-5 U ml −1 ) was incubated at 37°C and was subsequently assayed by measuring the absorbance at 540 nm. The α-amylase inhibitory assay was performed using starch as a substrate (1.0 w/v) with or without tannic acid (0.5 mg ml −1 ) or nanoparticles (0.5 mg tannic acid eq.…”
Section: Inhibition Of α-Amylase Activitymentioning
confidence: 99%